A review of the disruption of breastfeeding supports in response to the COVID-19 pandemic in five Western countries and applications for clinical practice - Sarah Turner; Bridget McGann; Meredith 'Merilee' Brockway (BMC, 2022)
Abstract Background The COVID-19 pandemic has significantly altered how breastfeeding support is provided, resulting in mixed breastfeeding outcomes and experiences for mothers. The World Health Organization has consistently supported breastfeeding from the beginning of the pandemic. However, recommendations from obstetrical and gynaecological societies within individual countries have varied in their alignment with this guidance, resulting in inconsistent recommendations. It is unknown how breastfeeding guidelines, maternal breastfeeding experiences, and breastfeeding initiation and duration compared across five Western countries. The current study is comprised of two parts, each with a different objective. Part One objective: to review pandemic-related changes in professional society guidelines on breastfeeding support in Australia, New Zealand, Canada, the United Kingdom, and the United States; and Part Two objective: to conduct a narrative review to summarize the evidence of how the pandemic has changed breastfeeding initiation, duration, and mothers' breastfeeding experiences during the pandemic in these five countries and provide recommendations for clinical lactation support. Methods We searched for indicators that are impactful on breastfeeding outcomes: skin-to-skin contact, rooming in, direct breastfeeding and breast washing, in the five countries mentioned above and compared these to the recommendations from the World Health Organization. Next, we conducted a narrative review of the literature from these five countries to explore how the pandemic altered breastfeeding outcomes and used this information to provide suggestions for clinical practice moving forward. Results Recommendations on the four practices above differed by country and were not always in alignment with the World Health Organization recommendations. Mother-infant separation after birth in the United States was associated with a lower prevalence of breastfeeding initiation and duration. While some mothers reported positive breastfeeding experiences during the pandemic, many mothers indicated negative experiences related to decreased social and professional support. Conclusions The pandemic can inform practice recommendations and can be viewed as an opportunity to permanently modify existing methods to support breastfeeding families. The use of virtual care increased during the pandemic and should continue with specific considerations for prioritizing in-person care. This will help to provide more timely and accessible support for breastfeeding mothers.